1994
DOI: 10.3109/03005369409086559
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of nimodipine, an L-calcium channel antagonist, in the treatment of tinnitus

Abstract: Thirty-one patients were drawn from a tinnitus clinic, screened for other medical problems and treated for 4 weeks with 30 mg nimodipine four times daily. Before and after treatment, the intensity of their tinnitus was assessed subjectively on a scale 1-10. Five patients reported to have a great improvement in their tinnitus whilst two claimed a worsening of the condition. Of the five positive responders, four were treated further with 30 mg nimodipine per day for 4 weeks and 60 mg per day for a further 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…Other drugs already studied for treatment of tinnitus are lidocaine,[12] antidepressants,[13] baclofen,[14] caroverine,[15] nimodipine,[16] clonazepam[17] and trimetazidine. [18] The introduction of these drug therapies have increased the success of tinnitus treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs already studied for treatment of tinnitus are lidocaine,[12] antidepressants,[13] baclofen,[14] caroverine,[15] nimodipine,[16] clonazepam[17] and trimetazidine. [18] The introduction of these drug therapies have increased the success of tinnitus treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Diuretics, 79 anticoagulants, 80 and vasodilators 81 have been tried without success. The drug betahistine, licensed in Europe but not the USA, is thought to help Ménière's disease by improving cochlear blood fl ow.…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…This has been primarily because of the complexity of the central nervous system, and the multifactorial causes of tinnitus. 14 Other drugs already studied for treatment of tinnitus are baclofen (improvement in about 9.7%), 15 caroverine (63.3%), 16 nimodipine (16.13%), 17 clonazepam (32%) 18 and trimetazidine (89%). 19 Different studies have shown that sensorineural tinnitus is caused by an imbalance of two neurotransmitters Glutamate and GABA in the auditory pathway.…”
Section: Discussionmentioning
confidence: 99%